Bioactive metabolites from Chaetomium aureum: Structure elucidation and inhibition of the Hsp90 machine chaperoning activity. Issue 1 (1st January 2015) - Kabbaj, Fatima Zahra; Lu, Su; Faouzi, My El Abbés; Meddah, Bouchra; Proksch, Peter; Cherrah, Yahya; Altenbach, Hans-Josef; Aly, Amal H.; Chadli, Ahmed; Debbab, Abdessamad
Graphical abstract